CGPRT - Information on coarse grains, pulses, roots and tubers - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
It was not until the early 1980s, that CGPRT crops (coarse grains, pulses, roots and tubers) were recognized by research and development workers as an alternative source of food which could improve the diets of both rural and urban people in the...